PENGARUH KUALITAS PRODUK, FITUR DAN DESAIN TERHADAP KEPUTUSAN PEMBELIAN MEBEL PADA CV. MUNAWIR FURNITURE DI JEPARA - Sutopo, Sutopo; Nuha, Ahmad Lu’lu’ Dhiyaun (Faculty of Economics and Business Diponegoro University, 2015)
Currently business competition furniture (furniture) lately relatively tight, so that each manufacturer must be able to provide the best quality products, so that consumers are satisfied, so that consumers willing to recommend to others to buy the production company. Purchasing decisions is the selection of two or more alternative choice of consumers in the purchase. If consumers have a choice between making a purchase and do not make a purchase or option to use the time, the consumer is in a position to take a decision. Based on the data, the average selling furniture CV. FURNITURE munawir Jepara decreased by 16,57 %. The decline was caused by various factors, such as product quality, design and features. The purpose of this study was to analyze the effect of product quality, design and features of the furniture purchase decisions. The population in this study is that consumers who buy furniture on the CV. Munawir FURNITURE, Jl. Raya Seokarno Hatta, Km 0,5, Tahunan, Jepara. The sample in this study was 100 consumers. The sampling technique in this study was done by using purposive sampling. Is the primary data type. Methods of data collection using the questionnaire. The analysis technique used is multiple regression. Results of analysis using SPSS showed that : Product quality proved positive and significant impact on purchase decision. Features proved positive and significant impact on purchase decision. Design proved positive and significant impact on purchase decision